Diagnóstico e revitalização da palma forrageira como alternativa da pecuária no cariri oriental da Paraíba - Pinto, Ivandro de Oliveira (2015)
The importance of the cultivation of cactus to the ranchers of the semi-arid northeast is due not only because she was dryland plant and therefore more potential for exploitation, but there is little use of fodder in the form of silage and hay in rainy periods. This forage is the only way to feed the flock in most localities of Paraíba semiarid region. The cochineal carmine (Dactylopius opuntiae) is decimating a large part and some places of the entire contents of this forage important. In view of this, it was necessary to carry out a quantitative diagnosis and / or quality of cultivated areas with traditional and its revitalization palm, with the introduction of new varieties resistant to this pest, in rural Caturité and Boqueirão, both located in micro eastern Paraiba cariri, which is the main objective determination. The territorial clipping understood twenty farms, ten located in the municipality of Caturité (7 25 '20' 'S; 36º01'41''W) and ten in Boqueirão (7º29'75' 'S, 36º07'87''W) being georeferenced using GPS and Google Earth satellite images. The diagnosis was the application of structured and semi-structured interviews and observations on the spot. Data analyzes were performed using statistical distributions of central tendencies measurements, dispersion and frequency. The main results show that the herd feeding is limited basically spineless cactus. The presence of cochineal carmine occurred between mid-2009 and 2010 and the decimation of palmais was very fast. The mealybug infestation levels Carmine are the order of 90% of palmais and Palm revitalization have proved the only alternative. However, in quantitative terms, the revitalized areas are much smaller than those of traditional cultivation. The plantations are recent and, therefore, the new varieties are still in the testing phase. Still, some producers reporting low productivity, while not withstand drought and have very thorn. The age range of respondents over 40 years, 60% have not either primary education and family income is low. Perception is almost unanimous about the importance of palm in the feeding of livestock, although unknown different by-products of palm. Most ranchers have not socioeconomic status and techniques to restore the area planted with traditional palm and therefore has no way to keep the flock and income to ensure a sustainable way their rural enterprise. There is a need to implement public policies to revitalize the cactus resistant cochineal carmine in Caturité and Boqueirão, to ensure the people in the countryside and therefore the dairy region of said micro.